2003
DOI: 10.1590/s0066-782x2003000200002
|View full text |Cite
|
Sign up to set email alerts
|

Exercise testing in hypertensive patients taking different angiotensin-converting enzyme inhibitors

Abstract: Monotherapy with trandolapril is more effective than that with captopril to control blood pressure during exercise in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…Carreira et al 94 compared the effect of two angiotensinconverting enzyme inhibitors in arterial hypertensive patients, and found that there was no difference in functional capacity between these two drug regimens, although trandolapril was slightly more effective than captopril in blood pressure control during exercise in arterial hypertensive patients. Other authors compared treatment with nebivolol to placebo during a 6-month period and failed to demonstrate the improvement of exercise capacity in patients with diastolic dysfunction.…”
Section: Antihypertensive Treatment and Functional Capacitymentioning
confidence: 99%
“…Carreira et al 94 compared the effect of two angiotensinconverting enzyme inhibitors in arterial hypertensive patients, and found that there was no difference in functional capacity between these two drug regimens, although trandolapril was slightly more effective than captopril in blood pressure control during exercise in arterial hypertensive patients. Other authors compared treatment with nebivolol to placebo during a 6-month period and failed to demonstrate the improvement of exercise capacity in patients with diastolic dysfunction.…”
Section: Antihypertensive Treatment and Functional Capacitymentioning
confidence: 99%
“…Como verificado por outros estudos 17,18 , os dados indicam que o comprometimento motor foi o fator limitante do teste de esforço físico aeróbico, sendo responsável pelas respostas das variáveis cardiovasculares ficarem bem abaixo dos valores esperados, já que não foram identificadas alterações na avaliação clínica do aparelho cardiorrespiratório Figura 2. Dispersão do índice de variabilidade da frequência cardíaca no domínio do tempo (pNN50) e do consumo pico de oxigênio (n=11) r= -0,61 e p= 0,04. bloqueadores de canais de cálcio e os inibidores da enzima conversora de angiotensina, apesar de aumentar a tolerância ao esforço 21 , deprimem as respostas da frequência cardíaca e da pressão arterial sistólica 22 . Em relação à modulação autonômica da frequência cardíaca, no presente estudo os valores de VFC no domínio da frequência, em unidades normalizadas, se apresentaram dentro da faixa de normalidade referida pela literatura, que considera valores entre 50 a 58 para o índice de baixa frequência, que representa a atividade de ambos os eferentes com predomínio simpático, e entre 26 a 39 para alta frequência, que representa a atividade parassimpática 23,24 .…”
Section: Discussionunclassified